PHYSICAL ACTIVITY AND CARDIOVASCULAR RISK FACTORS IN CHILDHOOD CANCER SURVIVORS - Slater, Megan E. (Pediatr Blood Cancer, 2014)
BACKGROUND: Childhood cancer survivors (CCS) are at high risk of developing treatment-related late effects, including cardiovascular disease and diabetes. Late effects can be exacerbated by low physical activity (PA) levels. Relationships between PA and cardiovascular risk factors during childhood have not been well described in CCS. PROCEDURE: PA and cardiovascular risk factors were measured cross-sectionally in 319 CCS and 208 sibling controls aged 9–18 years. Comparisons between CCS and controls and associations of outcomes with PA (dichotomized at 60 minutes/day or treated as continuous) were performed with linear regression. RESULTS: Among CCS, the high PA group had lower percent fat mass (24.4 vs. 29.8%, P<0.0001), abdominal subcutaneous fat (67.9 vs. 97.3 cm(3), P=0.0004), and abdominal visceral fat (20.0 vs. 24.9 cm(3), P=0.007) and greater lean body mass (41.3 vs. 39.5 kg, P=0.009) than the low PA group. Comparing CCS to controls, differences in waist circumference (P(interaction)=0.04), percent fat mass (P(interaction)=0.04), and abdominal subcutaneous (P(interaction)=0.02) and visceral (P(interaction)=0.004) fat between low and high PA groups were greater in CCS than controls, possibly due to greater overall adiposity in CCS. CONCLUSIONS: High PA in CCS resulted in an improved cardiovascular profile, consisting primarily of lower fat mass and greater lean mass, similar to that observed in controls. This suggests interventions directed to increase PA in CCS may reduce the risk of future cardiovascular disease.